Criatividade na escola: uma análise de propostas pedagógicas nos anos iniciais do Ensino Fundamental - Fleider, Mindla Monica Wrencher (2022)
This research investigated creativity in the school setting, specifically during the early years of elementary education. It focused on teaching for creativity through the teacher’s actions to stimulate student participation in creative processes, assuming that creativity is an innate ability that can be developed by all. This study investigated how teaching for creativity and stimulating creative thinking has been approached as pedagogical practice in a private school in Sao Paulo (Brazil) through the analysis of activity plans designed by multidisciplinary teachers who teach in the early grades of elementary school, as well as the ways these teachers conceive teaching for creativity. A qualitative methodology was employed — the examination of didactic plans, content and activities enabled the analysis of proposals that foster teaching for creativity. Data revealed that such practice is circumstantial and dependent on the teacher’s knowledge and availability, meaning that it is utilized in specific contexts. The conclusion is that teaching for creativity shows up timidly in activity planning and that the varying understanding of creativity among teachers influences the way they foster and enable creative thinking opportunities. Additionally, teacher planning does not necessarily articulate what takes place in the classroom, creating a fragile environment for teaching for creativity. There are several possible settings that enable the development of creative thinking in the classroom, however, these are not always prioritized in the activity plans analyzed